Microscopic analysis on optical gain of terahertz quantum cascade lasers - Liu, Tao (2013)
The effects of many-body coulomb interaction and non-parabolicity on optical gain of terahertz quantum cascade lasers are investigated based on the density-matrix model. The results show that many-body interaction and non-parabolicity effect all red-shift the gain spectrum and reduces the peak value. Furthermore, the interplay of various many-body effects that reveals the optical spectral redshift and reduction are mainly caused by the depolarization terms. The proposed model provides a comprehensive picture of optical properties of THz QCLs, not only enhancing our in-depth understanding of optical gain, but also enabling an accurate prediction of the device performance.